Risk identification and allocation in public-private partnerships : a New Zealand perspective : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Construction Management, Massey University, Auckland, New Zealand - Rasheed, Nasir (Massey University, 2024)
Public-Private Partnerships (PPPs) have become a prevalent solution for funding infrastructure projects amid declining public reserves. Despite their widespread adoption, not all PPP projects prove successful, often due to inadequate risk management. Recognizing the expertise of the private sector, including the New Zealand government, PPPs are increasingly utilized. However, there is a scarcity of specific research on PPPs in the local context, particularly in social infrastructure using the Design-Build-Finance-Maintain-Operate (DBFMO) delivery method. This thesis aims to address this gap by establishing a framework for improving risk management outcomes in New Zealand's PPP infrastructure projects, focusing on critical success factors, empirical investigations into risk identification, and the development and validation of a Fuzzy based risk allocation model to inform stakeholders' decisions. This research employed two distinct questionnaire surveys targeting industry experts from both public and private sectors, all possessing relevant experience in the local industry and PPP procurement. Given the absence of a precise population, a combination of convenience and judgment sampling, was utilized. A total of 43 and 58 PPP experts provided valid responses to two questionnaires. The sample size was considered appropriate, especially considering the relatively recent adoption of PPP in New Zealand. Additionally, comparisons were made with similar studies that employed questionnaire surveys to ensure validity. The collected data underwent various statistical analyses, including mean score analysis, Cronbach's alpha reliability analysis, independent sample t-test, and factor analysis. Subsequently, the fuzzy synthetic evaluation (FSE) method was applied to model risk allocation. In addition, the study included a set of semi-structured interviews to provide a practical and policy-making context for the research. Critical success factor rankings established through mean scores revealed approval and negotiation process, innovation and project complexity, client’s brief, project’s technical feasibility and strong private consortium to be five top ranked factors out of the 27 identified. Similarly, the top three risk allocation criteria (RAC) having very high importance (mean score greater than 4 on a scale of 5) were risk foresight, response to risk and minimise risk loss. Furthermore, factor analysis showed that the 9 identified RAC can be classified into three component groups namely risk management expertise, core risk management capability and risk management strategy. Recognizing the importance of principle of risk allocation, the proposed fuzzy based risk allocation model took into account the risk management capability of public and private sector. FSE was chosen for its adeptness in handling intricate multi-faceted challenges, particularly in the context of risk distribution decisions that involve the inherent vagueness within human cognitive processes. Due to their contentious nature in literature and different PPP projects, 16 risk were carefully chosen to be allocated via the model from a list of 35 risks initially identified. The findings indicate that for 12 of the risks, the distribution proportions between the government and the private sector are comparable. Risks associated with land acquisition and public opposition are predominantly assigned to the public sector, while risks linked to unforeseen geotechnical conditions and financing are predominantly allotted to the private sector. The results were validated using six interviews with highly experienced professionals within the New Zealand PPP scene. The outcomes of this study are anticipated to guide policymakers in formulating effective strategies for assigning risks and devising well-balanced risk sharing arrangements within PPP contracts, to achieve outcomes mutually agreeable to both the public and private sectors, ultimately enhancing the uptake of PPP projects.
Keywords: Public-private sector cooperation; Infrastructure (Economics); Risk management; New Zealand; Risk perception; Mathematical models; 330202 Building construction management and project planning